2003
DOI: 10.1107/s1600536803026412
|View full text |Cite
|
Sign up to set email alerts
|

1-tert-Butyl 2-methyl 4-(R)-hydroxypyrrolidine-1,2-(2S)-dicarboxylate

Abstract: Key indicatorsSingle-crystal X-ray study T = 160 K Mean '(C±C) = 0.002 A Ê R factor = 0.030 wR factor = 0.075 Data-to-parameter ratio = 11.2 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The most common 4-substituted Pro is the naturally occurring Hyp. With the electron-withdrawing hydroxyl group occupying the 4R position, Hyp prefers the exo ring pucker and adopts either the α R (Clegg et al 2003;Lübben et al 2014) or the P II conformation (Panasik et al 1994), exhibiting the trans imide bond. In contrast, 4S-hydroxyproline (hyp), which does not occur in nature, prefers the endo ring pucker with a cis amide bond and appears mostly in the δ-basin (Shoulders et al 2010).…”
Section: Crystal Structures Of Terminally Blocked 4-substituted Prolinementioning
confidence: 99%
“…The most common 4-substituted Pro is the naturally occurring Hyp. With the electron-withdrawing hydroxyl group occupying the 4R position, Hyp prefers the exo ring pucker and adopts either the α R (Clegg et al 2003;Lübben et al 2014) or the P II conformation (Panasik et al 1994), exhibiting the trans imide bond. In contrast, 4S-hydroxyproline (hyp), which does not occur in nature, prefers the endo ring pucker with a cis amide bond and appears mostly in the δ-basin (Shoulders et al 2010).…”
Section: Crystal Structures Of Terminally Blocked 4-substituted Prolinementioning
confidence: 99%
“…This ϕ torsion angle would also be compatible with polyproline II conformation and with the conformation at the i +1 position of type II and type VIa1 β-turns (( ϕ , ψ ) ~ (−60°, +120°)), which is the observed ( ϕ , ψ ) for other proline amino acids with electron-withdrawing 4 R -substitutents. 7a, 7e, 17a, 22a, 23a These data indicate the ability of this amino acid to promote compact conformations of proline and trans amide bonds ( ω = 180°).…”
Section: Figurementioning
confidence: 84%
“…7a, b, 21 These data, including the compact ϕ ~ −60°, suggest the application of 4 R -iodophenyl hydroxyproline in contexts where a more compact proline conformation (α R or PPII) is preferred, including at the i +1 position of type I, type II, or type VIa1 β-turns. 12a, b, 14, 22 Indeed, Raines and coworkers observed that related 4 R -hydroxyproline derivatives (-OH, -OMe, -OAc) can alternatively adopt α R or PPII conformations, with both conformations exhibiting favorable n→π* interactions. 22 These data also emphasize the conformational control possible with the judicious use of appropriate 4 R - and 4 S -substituted prolines, with each stereoisomer exhibiting divergent presentation of its functional group and distinct conformational preferences, suitable for structurally orthogonal applications (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations